CRANIAL NONMETRIC VARIATION OF MODERN KOREANS - M.ERDENE (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
In this study we present the results of cranial non-metric examination of modern Korean population. Cranial sample of modern Koreans, housed at the Department of Anatomy, Medical College of Korea University,South Korea was investigated for cranial and mandibular nonmetric traits. The sample consisted of 34 complete skulls, 38 skulls without mandible, 28 cranial vaults and 34 separate mandibles of 92 males and 38 females with ages ranging from infantile I to senile. Fifty nine discrete cranial traits were analyzed with respect to sex and side differences and frequency distributions. Results of the study show no significant sex and side differences in the frequencies of the cranial nonmetric traits. Tendency for sex difference was observed in the occipital torus expression and for the presence of the sutura incisive. Not statistically significant side difference was found for the presence of the parietal foramen, hypoglossal canal bridging, mylohyoid bridging and mandibular torus. Highly significant side to side correlation was found for the most of the traits (p<0.01). Insignificant correlation coefficients were found for zygomatico-facial foramen absent, epipteric bone, parietal foramen, foramen ovale incomplete, foramen spinosum open, jugular foramen bridging, clinoid bridging and accessory mental foramen.